FePO4 supported Rh subnano clusters with dual active sites for efficient hydrogenation of quinoline under mild conditions. Issue 3 (3rd January 2023) - Wei, Haisheng; Gao, Zhaohua; Cao, Liru; Li, Kairui; Yan, Xiaorui; Liu, Tiantian; Zhu, Mingyuan; Huang, Fei; Fang, Xu; Lin, Jian
Abstract : FePO4 supported Rh based catalysts exhibited excellent performance in the hydrogenation of substituted quinoline, attributed to the synergy between Rh subnano clusters and FePO4 support. Abstract : Chemoselective hydrogenation of quinoline and its derivatives under mild reaction conditions still remains a challenging topic, which requires a suitable interaction between reactants and a catalyst to achieve high performance and stability. Herein, FePO4 -supported Rh single atoms, subnano clusters and nanoparticle catalysts were synthesized and evaluated in the chemoselective hydrogenation of quinoline. The results show that the Rh subnano cluster catalyst with a size of ∼1 nm gives a specific reaction rate of 353 molquinoline molRh −1 h −1 and a selectivity of >99% for 1, 2, 3, 4-tetrahydroquinoline under mild conditions of 50 °C and 5 bar H2, presenting better performance compared with the Rh single atoms and nanoparticle counterparts. Moreover, the Rh subnano cluster catalyst exhibits good stability and substrate universality for the hydrogenation of various functionalized quinolines. A series of characterization studies demonstrate that the acidic properties of the FePO4 support favors the adsorption of quinoline while the Rh subnano clusters promote the dissociation of H2 molecules, and then contribute to the enhanced hydrogenation performance. This work provides an important implication to design efficient Rh-based catalysts for chemoselective hydrogenation under mild conditions.